Analisis Persepsi Mahasiswa Non Bahasa Inggris Terhadap Kebutuhan Bahasa Inggris Di Dunia Kerja - Ristia Wahyuningsih; Hanifah Aulia Kusuma; Heni Listyanti (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Some job vacancies in Indonesia include the requirement to have English language skills. This study aims to determine the perception of non-English students on the importance of English in the employment. This study used descriptive research method with quantitative and qualitative approaches and used perception theory to analyzed the data. Data collection techniques were carried out by survey and interview. The survey was filled by 100 students with various majors other than the English department. The research sample consisted of four students who were selected from filling out the survey. The results of the study show that 95% of 100 students think that English is important in the employment and 5% consider it unimportant. English is considered important because it is used for communication in work with foreigners or abroad. Someone who has English language skills can be a plus in his work. Meanwhile, English is considered unimportant in the employment because the variuos types of work so that not all require English language skills. These students’ perceptions are influenced by the environment, needs, experience, and insight.